The Meaning of Bibi Rangda Song in Calonarang Dance - Putra, I Dewa Gede Premasti Adhiguna; Gelgel, Ni Made Ras Amanda; Suryawati, I Gusti Agung Alit (E-Jurnal Medium, 2025)
Songs have been a communication media used by artists to express their feelings and often tell a story, it is no surprise that sometimes certain songs are used as a background song or soundtrack in a film, theatre, etc. the Bibi Rangda song which is known as tembang rare (kid songs) in Balinese people were found being used in Calonarang Dance, the type of dance notable of its sacred, magical and even scary atmosphere. This study will be focus on exploring the meaning of Bibi Rangda song in Calonarang Dance particularly on the scene when Rangda is breastfeeding a baby in a cemetery. This study use Roland Barthes’s Semiotic to analyse and draw the denotative, connotative and the myth on the using of Bibi Rangda song in Calonarang Dance with the descriptive-qualitative method using the constructivism paradigm. This study uses Roland Barthes’s Semiotic Theory to explore the meaning of Bibi Rangda song as the background song for the Calonarang Dance. The meanings of Bibi Rangda song in Calonarang Dance are meant to remind people to be grateful to God, watch over the way we think, say or do something, and to keep balance of this world along with everything in it.